The Effect of Cognitive Interventions with Drug Control on Emotional-Behavioral Problems in Adolescents - Mohsen Saeid Manesh (Journal of Global Pharma Technology, 2017)
The purpose of this study was to investigate the effect of cognitive intervention with drug control on emotional-behavioral problems in Adolescents. Being a quasi-experimental study, the research employed a pretest, posttest and follow-up (one month) design. The statistical population included bereaved Adolescents in yazd city in 2016. Of them, 30 students were selected via access sampling method, and were then randomly assigned into experimental and control groups. The measurement instrument was Goodman Strengths and Difficulties Questionnaire (Goodman, 1997). Experimental group received 8 sessions of cognitive intervention (each a 90-minute session). The results of analysis of covariance (with SPSS21) showed that cognitive intervention had significantly reduced emotional-behavioral problems in both in posttest and follow-up (P ≤ 0.05). Results also showed a significant difference between groups in all subscales including emotional problems, conduct problems, hyperactivity and peer problem in posttest and follow-up (P ≤ 0.05).Keywords: Cognitive interventions, Drug control, Emotional-behavioral problems, Adolescents.